If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/7(3x+2)-1/5(x+4)=2
We simplify the equation to the form, which is simple to understand
1/7(3x+2)-1/5(x+4)=2
Simplifying:
+ 0.142857142857*(3x+2)-1/5*(x+4)=2
Simplifying:
+ 0.142857142857*(3x+2)-0.2*(x+4)=2
Reorder the terms in parentheses
+( + 0.428571428571x + 0.285714285714)-0.2*(x+4)=2
Remove unnecessary parentheses
+ 0.428571428571x + 0.285714285714-0.2+*(+x+4+)=+2
Reorder the terms in parentheses
+ 0.428571428571x + 0.285714285714+(-0.2x-0.8)=2
Remove unnecessary parentheses
+ 0.428571428571x + 0.285714285714-0.2x-0.8=+2
We move all terms containing x to the left and all other terms to the right.
+ 0.428571428571x-0.2x=+2-0.285714285714 + 0.8
We simplify left and right side of the equation.
+ 0.228571428571x=+2.51428571429
We divide both sides of the equation by 0.228571428571 to get x.
x=11
| 14=7x+6-5x | | 5(3x-1)=19 | | x(x-4)=221 | | 4x-3y=26 | | 8u+2=4u-10 | | b-1+3b=22 | | 0.2p-1.8=2.3p-4.5-1.8p | | 0.06x+0.03(100+x)=4.35 | | x^2000+x^1000-2=0 | | 3y^2-11y-10=0 | | 5-3x=3x+15 | | 5-3x=3x-15 | | 6(x+3)=2(x+27) | | 0.007(x+3)=0.008x+0.016 | | 5[7-5(6b)]-7=7[5(7b-6)+4]-50 | | X+3=4x-7 | | x^2000+x^1000-2 | | 11=9x+2-6x | | n-20=-7 | | 4c-2=2 | | 0.04(y-1)+0.08=0.02-0.01(70) | | x÷4=3 | | 5(6-3)=75-5x | | 4x^3+8x^2-9x-18=0 | | (10y^3-5y+8)-(-3y^3-6y^2+6y-13)= | | 6≥x3 | | 9-6x-4=45 | | x^4+x^2-2 | | -4x+7(2x+3)=7x+36 | | 2x-6=54-8x | | (13y^3-4y+11)-(-6y^3-7y^2+7y-16)= | | 3(x-6)-6(x-3)=x+7-(x-2) |